Manajemen Kesiswaan Pada Sekolah Inklusi - Achmad Hufron; Ali Imron; Mustiningsih Mustiningsih (Universitas Negeri Malang, 2016)
Abstract: The purpose of this study is to describe the student management at inclusion school. This study used a qualitative descriptive approach and multi-site studies design. The techniques of the study were collecting data used interviews, observation and documentation. Data analysis was divided into two phases of data analysis; those are data analysis site and site across data analysis. In checking validity of the data in this study used three kind of validities that are credibility, dependability, and confirmability. Based on those technique data analyses, it is found across the site as follows. First of all, the implementation of new admissions both regular students and students with special needs conducted in line with the new students enrollment requirements of Dikpora Kebumen. In state Elementary School 1 Surotrunan, new students who have special needs were selected and accepted, the range is for students with low till medium needs. In the other hand, State Elementary School Pecarikan using a system of promotion. Secondly, students are placed in a class, moreover, students' grouping is based on their intelligence, academic ability and special needs. Thirdly, student treatments are given through some habitual activities, extracurricular activities, and incidental activities. Schools require guider (shadow) on each ABK's. Key Words: management, student, educational inclusion Abstrak: Tujuan penelitian adalah mendeskripsikan manajemen kesiswaan pada sekolah inklusi. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan rancangan studi multi situs. Teknik pengumpulan data dengan wawancara mendalam, observasi, dan studi dokumentasi. Analisis data terdiri atas analisis data dalam situs dan analisis data lintas situs. Pengecekan keabsahan data menggunakan tiga kriteria, yaitu kredibilitas, dependabilitas, dan konfirmabilitas. Temuan lintas situs dalam penelitrian ini sebagai berikut. Pertama, pelaksanaan PPDB baik siswa reguler maupun siswa ABK dilaksanakan bersamaan sesuai dengan juklak PPDB di SDN 1 Surotrunan, siswa ABK di seleksi yang diterima adalah ABK yang mempunyai jenis kebutuhan ringan ke sedang, sedangkan SDN Pecarikan menggunakan sistem promosi. Kedua, siswa ditempatkan menjadi satu kelas, pengelompokan siswa berdasarkan kecerdasan, kemampuan akademik, dan kebutuhan khusus. Ketiga, pembinaan kesiswaan dilakukan melalui kegiatan pembiasaan, ekstrakurikuler, dan kegiatan insidental. Sekolah mewajibkan pendamping (shadow) untuk siswa ABK. Kata kunci: manajemen, kesiswaan, sekolah inklusi